Implementation of the internal quality assurance system (SPMI) in junior high school - Sari Marlina; Edi Harapan; Nila Kesumawati (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
Improving the quality of education at SMPN 1 Betung is carried out through the implementation of an internal quality assurance system. The research objective was to describe the implementation of the internal quality assurance system at SMP Negeri 1 Model in Betung, Banyuasin Regency. The descriptive qualitative research method is the type of field study. The research subjects were the principal, deputy principal, administrative staff, operators, and teachers of SMPN 1 Betung. Data collection techniques were observation, interviews, and documentation. Data analysis techniques are in the form of collection, reduction, presentation, and conclusion. Data validity checks include credibility, transferability, dependability, and confirmability tests. The results showed that the implementation of the internal quality assurance system of SMP Negeri 1 Model in Betung, Banyuasin Regency was carried out in accordance with the instructions for the SPMI Dikdasmen Kemendikbud developed by the government through the model school program and pengimbasan. The implementation stage, namely preparation consisting of training, preparation, and socialization. SPMI implementation includes mapping, fulfillment of plans, implementation, monev, and setting new standards, mentoring, monitoring, monitoring and evaluation.